Multipoint Measurement of Fine‐Structured EMIC Waves by Arase, Van Allen Probe A, and Ground Stations. Issue 23 (8th December 2021) - Matsuda, S.; Miyoshi, Y.; Kasahara, Y.; Blum, L.; Colpitts, C.; Asamura, K.; Kasaba, Y.; Matsuoka, A.; Tsuchiya, F.; Kumamoto, A.; Teramoto, M.; Nakamura, S.; et al.
Abstract: We examined the growth and propagation of fine‐structured electromagnetic ion cyclotron (EMIC) waves related to time‐varying density irregularities using multipoint measurement data observed by Arase, Van Allen Probe A, and two ground‐based induction magnetometers (Gakona and Dawson) during a field line conjunction event on April 18, 2019. We analyzed the wave data obtained by the aforementioned spacecraft and stations, and found that the appearance of fine structures in the observed EMIC waves clearly coincided with the ambient electron density irregularities in the magnetosphere, which can cause periodic wave growth and waveguiding on their propagation. Furthermore, we found that the latitudinal widths of the EMIC wave activity region and the wave propagation duct were ∼185 km and less than 80 km at an auroral altitude of 100 km, respectively. We also found thermal ion heating ( < 200 $< 200$ eV/q) during the EMIC wave activity. Plain Language Summary: Electromagnetic ion cyclotron (EMIC) waves are an important plasma waves that control energetic ion and relativistic electron precipitations in the terrestrial inner magnetosphere. We investigated the growth and propagation of fine‐structured EMIC waves observed simultaneously by two spacecraft (Japanese Arase and U.S. Van Allen Probe A) and two ground stations (Gakona and Dawson). The two spacecraft orbited along the same field line, and we measured the same fine‐structured EMIC waves in different geomagnetic latitude regions. The same EMIC waves were observed at the two ground stations located near the magnetic footprints of the two spacecraft. We report that the periodic growth of the observed EMIC waves was associated with the time‐varying electron density irregularity in the midlatitude region. Additionally, we analyzed the spatial scale of the observed EMIC waves and their contribution to the thermal ion heating. Key Points: The simultaneous multipoint observation of fine‐structured electromagnetic ion cyclotron (EMIC) waves was achieved by Arase, Van Allen Probe, and two ground‐based stations The growth of the observed fine‐structured EMIC waves was associated with ambient electron density irregularities in the midlatitudes We investigated the spatial scale of the observed EMIC waves and their contribution to ion heating by utilizing the multipoint measurement